2022
DOI: 10.1002/ccd.30336
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure with the II generation Ultraseal device: An international registry. The LIGATE study

Abstract: Objectives To assess feasibility and safety of second‐generation left atrial appendage closure (LAAC) Ultraseal device in patients with nonvalvular atrial fibrillation (NVAF). Background LAAC with first‐generation Ultraseal device (Cardia, Eagan, Minnesota) has been shown to be a feasible therapeutic option in patients with NVAF. However, there is a paucity of data regarding the novel second‐generation Ultraseal device. Methods All patients with NVAF undergoing second‐generation Ultraseal device implantation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…One device-related perforation and one severe leak were noted, with total procedural success achieved in 94%. 4 These success rates compare favorably to the firstgeneration device reported by Asmarts et al, 3 as well as to other LAAC devices. In-hospital major adverse events (MAEs) occurred in 6%, including major bleeding in two patients and a minor stroke in one patient.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…One device-related perforation and one severe leak were noted, with total procedural success achieved in 94%. 4 These success rates compare favorably to the firstgeneration device reported by Asmarts et al, 3 as well as to other LAAC devices. In-hospital major adverse events (MAEs) occurred in 6%, including major bleeding in two patients and a minor stroke in one patient.…”
supporting
confidence: 71%
“…The sail covering polyester layer is now on the luminal surface of the device and the articulating joint has a lesser degree of movement to aid in deployment and retrieval. 4 According to this multicenter, retrospective, single-arm study, device and technical success was observed in 100% and 96% of patients, respectively. One device-related perforation and one severe leak were noted, with total procedural success achieved in 94%.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In a multicenter international registry including seven European centers and 52 patients undergoing second-generation Ultraseal device implantation, technical success was achieved in 96.1% patients. 7 The primary safety outcome of in-hospital major adverse events, defined as a composite of all-cause death, stroke or transient ischemic attack, systemic embolism, major bleeding, MI, major vascular complication, or device embolization, was found in 5.8% of patients. In the study, 34 patients underwent follow-up TEE at a median duration of 61 days; 2.9% patient had a peri-device leak >5 mm and no patients had a device-related thrombus (DRT).…”
Section: Ultraseal Devicementioning
confidence: 99%